Assessing radonotherapy effectiveness and modulated steroidogenesis in experimental chronic endometritis model - A. E. Chernova; O. V. Remneva; I. P. Bobrov; A. V. Lepilov; O. N. Mazko; O. G. Makarova; N. M. Semenikhina; O. V. Rozhkova; I. V. Grebtsov; D. A. Baranov; S. A. Antonova; V. V. Baranova (IRBIS LLC, 2023)
Aim: to evaluate therapeutic efficacy and modulated steroidogenesis after radon therapy in experimental chronic endometritis model.Materials and Мethods. A therapeutic effect related to radon mineral waters was studied experimentally. The water radon concentration was 5.4-6.2 nCi/dm3. The experimental endometritis was induced in laboratory Wistar line rats (n = 40) inoculated with intra-uterine self-fecal suspension. Experimental group animals (n = 10) received a wide-spectrum antibiotic Ceftriaxone within 7 days followed by applying 10 procedures of radon therapy one a day and from day 41, the first procedure lasting 5 minutes, the second - 8 minutes, the third - 10 minutes, with all other procedures - for 15 minutes. Comparison group I animals (n = 10) received antibacterial therapy, radon therapy and 10 procedures of peloid therapy with natural salt-saturated medium sulfide silt therapeutic mud according to a radon therapy regimen. Сomparison group II (n = 10) received antibacterial and peloid therapy according to comparison group I regimen. Control group (n = 10) received no treatment. Inflammatory signs were assessed by endometrium histology study. The venous steroid hormones levels were analyzed by enzyme-linked immunosorbent assay.Results. In experimental vs. control group, it was found that endometrial diffuse infiltrate was of lower density comprising 125.4 ± 8.1 vs. 180.7 ± 9.0 immunocompetent cells (by 30.7%; p = 0.002), whereas in comparison group I, density of inflammatory infiltration was minimal (reduced by 88.7 % compared to control group; p < 0.001) and reached 20.5 ± 1.8 cells. In the experimental group as well as comparison groups I and II vs. control group, a significant increased level of serum progesterone was observed after treatment (p = 0.008). When using a radon therapy in experimental group, it resulted in a more prominent rise in progesterone level compared to peloid therapy in comparison group II. Radon balneotherapy was found in main control group to elicit a significant declined estradiol level (p = 0.008), but not in comparison groups I and II featured with no significant change in estradiol level compared to control group.Conclusion. Radon therapy exerts an anti-inflammatory effect in experimental chronic endometritis model. Radon therapy combined with peloid therapy has a potentiated effect. The use of radon balneotherapy is accompanied by significantly increased progesterone and decreased estradiol level suggesting to conduct clinical trials for confirming its effectiveness in patients with reproductive dysfunction including diseases accompanied by hyperestrogenism.